(untitled) (NAU Journal of Library and Information Science, 2021)
The study sought to determine undergraduates’ perception of use of library course as an aid to use of information resources in university libraries in North West, Nigeria. Five research questions guided the study. Descriptive survey design was adopted for the study. The population of the study was 9,462 from which 358 was drawn as sample using proportionate stratified sampling technique. The instrument for data collection was a questionnaire. Out of the 358 questionnaire distributed, 348 representing 97% were returned and found usable for the study. Data collected was analysed using statistical mean to answer the research questions with criterion mean placed at 2.50. Findings of the study showed that students’ perception of the use of library course as an aid to their use of various information resources in circulation, catalogue, reference, serials and e-resources were all positive. Based on the findings, some recommendations were made which include that university libraries should make the course a practical oriented one to enable undergraduates make effective use of the library resources. Furthermore, ICT skilled and competent librarians should teach the e-resources aspect of the course. It was also recommended that those who teach this course should be practicing librarians from the university library. It was also recommended that the course content as it concerns the use of the library catalogue and reference materials should be revised to enhance a better and effective use of library resources. Keywords: University Library, Undergraduates’ Perception, Library Use, User education, User Aid, Library Resources, North West Nigeria. Introduction The university library is a very important component of the university system, hence, Anyaegbu, (2016) posits that the university library is the academic nerve centre of the university. This is because all the teaching, learning and research going on in the university revolve around the library collection. It serves both staff and students of the institution. The Federal Government of Nigeria (2014), in its National Policy on Education stressed the need for a well-stocked library in institutions of higher learning. In line with this, no university takes off without a library to service the academic programme of the university. The university library acquires various kinds of information resources both in print and non-print media to support teaching, learning and research in the university. Acquired materials are processed by librarians for use by students and other library users. These library resources after processing are arranged at various designated section according to their forms and subject. For example, the library catalogue informs the user what book by a particular author, title or subject is available in the library and where to locate it on the shelf. Information resources acquired by the library include, books, journals, newspapers, e-resources, encyclopedias, dictionaries, audio-visual, amongst others. The various library operations it takes to access these materials include the library catalogue, circulation, reference, serials services among others. Circulation services of the library is the first point of contact of the user with the library. Users of library are meant to register with the library before they are allowed access to the library resources. Library materials are loaned to users at the circulation section. This underscores the importance of circulation services for effective use of the university library by the undergraduates. Hence for the undergraduates to know about these resources and how to utilise them maximally, they need to undertake the “Use of Library.” Course. Similarly, the library catalogue is the list of information resources acquired. It serves as a link between the users and the library resources. The library catalogue is the product of cataloguing and classification processes aimed at providing the bibliographical details such as the author, title, edition, pagination, among others as well as the class number/ notation mark of the acquired materials. It directs the user to the shelf location of the information sought. It is thus a retrieval tool. Usually card catalogue entries are arranged by author, title and subject. With the advent of ICT in library operations, there is now an online version of library catalogue known as Online Public Access Catalogue (OPAC) which makes searching for materials easy and quick. There is thus a need to teach students the use of library course to help them understand and use the library catalogue and by implication library resources effectively. Reference services is rendered for those information resources that are not meant to be read page by page, hence the name reference. These information resources are different from textbooks. Reference resources include encyclopedias, dictionaries, index, and abstracts, bibliography, yearbooks, almanacs, directories, guides, maps/atlases, handbooks, manuals and so on. They provide different information ranging from background information (encyclopaedia) to meaning, origin of words of different languages (dictionaries); summary of original work-with its bibliographic description (abstract); directions to places (directories); past year events (yearbooks) and how “to fix”, “do things” and so on. While serial resources are those library resources that appear at regular or irregular intervals whose publication is meant to be continuous. These resources constitute a very important source of information as they contain current information. Prominent among them are journals, technical reports, newspapers and so on. Users need to be aware of these resources and how to utilize them properly. Electronic information resources (e-resources) are simply information resources in digital format. They can be accessed online or offline. Online, when Internet connectivity is required to use them and offline when Internet connection is not needed. Some e-resources are packaged in databases. They include e-journals, e-books, CD-ROMs, online and offline databases like EbscoHost, HINARI, Library OPAC, Science Direct, AJOL among others. Accessing these materials require digital information literacy skills which include computer literacy, search skills, downloading and uploading skills else they may not be effectively utilised, hence the need to teach the course, Use of Library. Use of the library course assume many names such as user education , library instruction, library orientation, library guide. The National Universities Commission (NUC) named it GST 121-Use of Library Study Skills and ICT. The NUC Benchmark, makes it mandatory for all universities in Nigeria to include library literacy course in their curriculum. For example, Federal University Gusau, Zamfara State offers the course as GST 105: Use of Library, Study Skills and ICT. It is a two credit unit course with a rich content. Its content is as follows: brief history of libraries, library and education, university library and other types of libraries, study skills, reference services, types of library materials, using library resources (e-learningand e-resources among others), understanding library catalogue(card and OPAC) and classification, copyright and its implications, database resources, bibliographic citation and referencing, development of modern ICT, hardware and software technology, input devices, storage devices, output devices, communication and Internet services,word processing skills and so on. The use of library course is designed to teach students the range of information resources in the library and how to access and make effective use of them to satisfy their information and research need. This study was carried out in federal Universities in North West Nigeria. The zone has seven states with 15 universities. North West Nigeria is one of the six geo-political zones in the country and it is made up of seven states namely, Jigawa, Kano, Kaduna, Katsina, Zamfara, Sokoto and Kebbi. This zone is populated by the Hausa and Fulani tribes, with Islam as the predominant religion. The occupation of the people is predominantly farming, cattle rearing, fishing among others. Statement of the Problem All the teaching, learning and research going on in the university revolve around the library collection. Quite a lot is invested to ensure that every discipline is covered in the acquisition of information resources in the library. A well-equipped but underutilized library is as good as a storehouse and a near waste of limited financial resources. In recognition of the crucial role the university library plays in the academic programme of the university, use of the library course was designed to assist students acquire the necessary skills needed to not only access and use the library resources but to also enhance their academic performance and lifelong education. Unfortunately, preliminary investigation carried out by the researcher shows that despite the provision of library materials and user education by libraries, undergraduates’ utilization of these resources is low. This may be either that students do not really appreciating the value of the university library or its impact on their academic pursuit or that the teaching of the course has not made much impact. This low usage may have resulted in poor academic performance and research output by undergraduates of Nigerian universities. However, the perception of the undergraduates on the use of library course as an aid to use of library resources in university libraries has not been ascertained. This study was set to find out undergraduates’ perception of use of library course as an aid to their use of resources in universities in North West, Nigeria. Purpose of the Study The main purpose of this study was to find out undergraduates’ perception of use of library course as an aid to their use of resources in universities in North West, Nigeria. Specifically, the study sought to determine undergraduates’ perception of use of library course as an aid to: 1. Their use of library circulation services. 2. Their use of library catalogue resources. 3. Their use of library reference resources. 4. Their use of library serials resources. 5. Their use of library E-resources. Research Questions The following research questions guided the study: 1. What are undergraduates’ perceptions of use of library course as an aid to their use of circulation services? 2. How do undergraduates perceive use of library course as aid to their use of library catalogue? 3. How do undergraduates perceive use of library course as an aid to their use of reference resources? 4. What are undergraduates’ perceptions of use of library course as an aid to their use of serials resources? 5. What are undergraduates’ perceptions of use of library course as an aid to their use of e-resources? Review of Related Literature According to Unegbu and Otuza (2015), a university library is a kind of academic library that serves the information needs of the university community through provision of information resources that supports learning, teaching and research. Fagbola (2015) defines the university library as the focal point of academic and research activities in the university. This supports the assertion that university library is the heartbeat of the university. It is the pivot upon which all academic activities revolve. Library resources according to Adeyemi (2010) is in two ways namely, material resources which include books, journals, CD-ROMs, audio-visual, micro film, microfiche and so on, and human resources as the staff – professional librarians, para-professionals, and supporting staff. This definition divides library resources into two; human and material. Without human resources the material resources cannot be used, because it is the human beings (library staff) that will put the various material resources in place for use. Koffar (2009) included audio-visual material of various types, pictures, or charts, books, radio, television, type writing machine, computer, chalkboard, and projectors. This is to say that, library resources are human and material enablers deployed by the library in order to perform its duties and services to users aimed at achieving the objectives of the library and its parent institution. While the human resources comprise of all human engaged by the library either as full time staff, part time or consultant/resource person, the material resources includes the physical infrastructure, information resources, equipment, working tools among others. Use of Library Course The concept of “use of library” or “user education” or “study skills “has developed in the area of Library Science. This development is a radical change towards better use and dissemination of information in the library. Igbena in Ogbuiyi, Oriogu and Ogbuiyi (2013) states that user education is a process of making library users learn how to make effective and efficient use of library resources and information through the acquisition of skills in identification, location, search, retrieval and exploitation of information. User education according to Ilo, and Idiegbeyan-ose, (2011) comprises the gamut of activities ranging from education to individual instruction which libraries provide to users to enable them maximize the library resources and services. Klaib in Ilo and Idiegbeyan-Ose (2011) opine that user education programme is organised in order to inculcate in users, library use skills such as bibliographic education and information literacy skills. There are various kinds of user education adopted by university libraries, for example, library orientation (a talk on use of the library given by the University Librarian to fresh students during the orientation programme), library tour (where students are grouped and taken on a tour of the library by a designated library staff to acquaint them with various sections and operations of the library), library guide (document giving brief description of the library aimed at helping the students have knowledge of the university library), use of library course (a General Study course which is the focus of this study) a compulsory 2 credit unit course designed to teach undergraduates how to make effective use of the library and acquire other study skills that will enable them function well in this information age. Use of library can therefore be defined as a course of study designed to teach students what the library is and the necessary skills needed to attain competency in the use of library and other sources of information even long after graduation. Research Methodology Descriptive survey research design was adopted for this study as it will help in describing the undergraduates’ perception of use of library as aid to their use of various resources in universities in North West Nigeria using a small sample population.The population of the study was 9,462 comprising all the 300 level registered users of the libraries in seven Federal Universities in North West Nigeria for the 2017/2018 academic session. The choice of 300 level was because they had offered the use of library course at their 100 level and had spent additional year of study (200 level) in the University. The sample size was 358. Proportionate stratified sampling technique was adopted to ensure equal participation of the subgroups in line with their respective population. Questionnaire was the instrument for data collection. A total of 358 questionnaires were distributed and 348 were returned, this represents 97% of the sample population. The returned questionnaire was subsequently organized and analysed using mean and standard deviation. Mean score of 2.50 and above was considered positive on any response to an item whereas below2.50 was considered negative response to an item. SPSS (version 23.0) was used for all computations. Four point rating scale was used with the response mode of Strongly Agree (SA) = 4, Agree (A) = 3, Disagree (DA) = 2, and then strongly Disagree (SD) = 1. Results Research question 1: What are undergraduates’ perceptions on use of library course as an aid to their use of library circulation section/resources? Table 1 : Mean Rating of the Undergraduates’ Perception of Use of Library Course as an aid to their use of Circulation Services As shown by the mean scores of the items in table 1 describing undergraduates’ perceptions on use of library course as an aid to their use of library circulation, it is clear that undergraduate students have positive perception of all the items. This is evident from the mean rating of all the items which are all higher than the criterion mean score of 2.50. Item 3 has the highest mean score of 3.35 with an STD of .771. This is followed by item 1 which has a mean score of 3.33 with STD of .719. The table also revealed that item 2 has the least with 2.93 mean and .901 STD. The grand mean of 3.23 revealed that the Undergraduates’ Perceptions on use of Library Course as an aid to their use of Library Circulation Section/Resources is highly rated. Research question 2: How do undergraduates perceive use of library course as an aid to their use of library catalogue resources? Table 2: Means Rating of How Undergraduates Perceive Use of Library Course as an Aid to their Use of library Catalogue Responses in table 3 shows that undergraduates know the various access points such as title, subject and author. This received a mean score of 3.49 and STD of .713 while, item 2 shows that they understand how to locate library resources using library catalogue. All items in the table received positive mean score above 2.50. Therefore, result from the table with the grand mean of 3.28 revealed that undergraduates have a positive perception of use of library catalogue as aid to their use of library. This is as a result of the use of library course which they received. Research question 3: How do Undergraduates Perceive use of Library Course as an aid to their Use of Library Reference Resources? Table 3: Mean Rating of How Undergraduates Perceive Use of Library Course as an Aid to their Use of Reference Resources As shown in table 3, item 10 have a mean score of 3.29 and .731STD for consulting a reference librarian when necessary. Item 8 scored received a mean score of 3.21 indicating good perception of the undergraduates use of library course as an aid to their use of reference resources. Items 2 (use of abstract) and 6 (use of thesaurus) received mean scores of 2.93 and 2.69 respectively. They are the least rated although they are above the criterion mean score of 2.50. The table shows that the undergraduates have good perception of the use of library course as an aid to their use of reference resources of the university library. Research question 4 : What are Undergraduates’ Perception of use of Library Course as aid to their use of Library Serials Resources? Table 4: Mean Rating of Undergraduates’ Perceptions of use of Library Course as aid to their use of Serials Resources Responses from the participants in table 4, shows that the undergraduates understanding of serials management is good. Specifically, items 1 (serial management) and 3 (enhanced knowledge of journal for academic) both scored 3.08 respectively, item 1 scored .821 for STD, item 3 has .797. The table shows that Item 2 scored the least mean (2.59) with .992 STD. Generally, the grand mean of 3.02 indicated that all of them responded positively in strong agreement with all statements as they all were above the acceptable mean of 2.50, hence, the result from the table revealed that the use of library course is an aid to their use of library serials resources in the university libraries. Research question 5 : What are Undergraduates’ Perception of use of Library Course as an aid to their use of E-Resources? Table 5: Undergraduates’ Perceptions of use of Library Course as an aid to their use of E-Resources in the university library Respondents from the participants in table 5 revealed that all the participants agreed to the statements on the items. Item 3 received 3.27 mean and .838 STD on the statement on enhancement of knowledge of ICT resources (e-resources). Whereas items 4 and 10 scored 3.15 and SD .831 and .853 respectively attributing to their enhanced skills of their database search and knowledge that changed their traditional views of managing information resources. However, items 1 and 8 scored the least mean. The result generally shows strong positive perception from the participants on the statements indicating use of Library Course as an aid to their use of E-Resources of the university library. Discussions of Findings Undergraduates’ Perceptions of use of Library Course as an aid to their use of Circulation services This finding showed that undergraduates perceive use of library course as aid to their use of circulation Services. This means that the course, use of library impacted the undergraduate to make use of the circulation services which is the gateway to the library holding. Their understanding of various services offered by the section such as library registration, charging and discharging, library rules, library fines as well book reservation makes them to see the course, use of library as being beneficial to them in registering with the library so as to even enter the library in the first place, obey library rules, borrow library resources etc. Inter-library loan which has a low mean score compared to other items could be that they perceive it to be cumbersome. Indeed, the use of library course tends to be beneficial to undergraduates of North West Nigeria because it helps them to make optimal use of their circulation services. Undergraduates’ Perceptions of use of Library Course as an aid to their use of Library Catalogue This finding indicates that undergraduates’ perception of the use of library course is an aid to their use of library catalogue resources. The library catalogue is the index of the library holding. It provides the link between the library resources and the user. The positive rating it received is an indication teaching of the use of library course impact positively on the students Undergraduates’ Perceptions on use of Library Course as an aid to their use of Reference Resources The result here showed that the undergraduates have positive perception of use of library course as an aid to their use of library reference resources. This means that the course helped the students to make proper use of reference resources. Reference resources are important and indispensable library information resources needed for a successful academic career. Reference sources include, dictionaries, which gives insights into words (meaning, origin, pronunciation and so on), encyclopedias which provides background information either in general knowledge or in specialized areas, government publications, projects, thesis and dissertations, handbooks, manuals, directories, guides, abstracts, indexes, bibliographies, biographies/autobiographies, atlas, almanacs, maps, gazetteers, yearbooks, among others. They are specially written resources with varied and authentic information. Reference resources as indispensable information resources in the university library should be given adequate attention by library management so as to improve the overall optimal usage of the resources. Undergraduates’ Perceptions on use of Library Course as an aid to their use of Serials Resources Students perception of use of the serial collection in the universities studied was positive. Serials are important research material in the university library. Their use of journal and technical reports seem to be higher probably because the group studied were undergraduate students in their final year. Undergraduates’ Perceptions on use of Library Course as an aid to their use of E-Resources The result of the finding on e-resources was also positive showing that undergraduates perceive use of library course as aid to their use of library e-resources. E-resources has made access to current research reports easier and much more available in high quantity, therefore without effective teaching and learning of the use of library course, undergraduates may still be finding it difficult to use their university library e-resources. The course has helped the students to know various e-resources databases for their academic and other information needs. Conclusion The following conclusions were drawn based on the findings of the study: The findings of this study provides important and verifiable data into undergraduates’ perception or how they see the course, use of library viz- a –viz their understanding and use of library circulation services, catalogue, reference, serials and e-resources. The finding of the study showed that undergraduates perceive use of library course as an aid to their use of resources in university libraries in North West Nigeria. It can therefore be inferred that undergraduates who offered the course, use of library will use library circulation services more effectively. With the exception of inter-library loan service, the understanding of others is quite impressive. Again, the perception of undergraduates of the course, use of library as aid to their understanding and use of library catalogue resources is that it actually aided them in their use of library catalogue. However, literature reviewed showed that some students face constraint in seeking information because of their lack of knowledge on how to use the catalogue. Nevertheless, this does not invalidate the result of this study. It can therefore, be concluded that undergraduates who partake and understand the course, use of library will use library catalogue and other retrieval tools more effectively. In addition, the undergraduates perceive use of library course as aid to their use of library reference resources. Furthermore, it can also be concluded that undergraduates’ who receive the course use of library are in a better position to appreciate and use library e-resources, this is because the findings of this study showed that undergraduates responded positively to the use of library course as an aid to their use of library e-resources. Recommendations The following recommendations were made from the findings of the study: 1. Teachers of use of library course should put in more effort in teaching undergraduates’ how to utilise the information resources and services available to them in the circulation section, as well as explore how inter library loan services can be included in circulation services. 2. The use of library course should be effectively used to introduce undergraduates on how to understand the various aspects of the library catalogue like the author, title and subject entries. 3. There should be increased efforts to make undergraduates understand and use the reference resources with much emphasis on abstract, thesaurus, encyclopedias, Almanac, among others. 4. Emphasis should be placed on better ways to access the serial collection for enhanced research. 5. Skilled and competent e-librarian should deliver the ICT aspect of the use of library as this will help impart the undergraduates with the right skills they need to search and retrieve the vast e-resources available in the university. 6. The librarians at the university library should be allowed to teach use of the library for a better utilization of the information resources in the library. 7. Information literacy should be incorporated in all curriculum on use of library in all Nigerian universities. References Aderibigbe, N. A., &Ajiboye, B. A. (2013). User education programme as a determinant of electronic information resources usage in NimbeAdedipe University library, Nigeria.ElectronicLibrary, 31 (2),244-255 . Retrieved From:https://www.researchgate.net Adeyemi, O. T. (2010). The school library and students’ learning outcomes in secondary schools in Ekiti State Nigeria. Asian Journal of Business Management, 2 (1), 1-8. Agbola, I. O. &Bamigboye, O. B. (2011). Students level of study and use of library resources in Nigerian Universities: a comparative study. Library Philosophy and practice – e-journal.Retrieved from http://www.webpages.uidaho.edu/ mbolin/agboola-bamigboye.htm Aghadiuno, O., Agbo. A. &Onyekweodiri, U. (2015). Accessibility and use of Serials and other continuing resources in two university libraries. International Journal of Multidisciplinary Research and Development, 2 (5),93-97. Retrieved from: www.allsubjectjournal.com Aliyu, Y. S. (2004). Library stock as factor for improving quality education in Nigerian Colleges of Education. Borno Library Archival and Information Science Journal, 3 (1 & 2), 17-19. Amkpa, S. A. (2000). Students’ use of University of Maiduguri Library: An evaluative study. Gateway Library Journal, 2 (3), 70-80. Amkpa, S. A. & Imam, A. (2011). Library instruction programme as a correlate to student catalogue use in Colleges of education libraries.Library Philosophy and Practice (e-journal). Retrieved from http://cel.lip.edu/ Anyaegbu, M.I. (2016) Rationale for a course on use of library and information literacy. Use of library and information literacy for higher education. Awka; Potential Books Azubogu, N. C. (2007). ICT: A catalyst for effective library services delivery in Imo State. A Journal of Nigerian Language and culture. 9 (1), 207-213 Chan, S. (2003). Making Information literacy a compulsory subject for undergraduates: the experience of the University of Malaya . IFLA Journal, 29 (4), 328-335. Coleman, L. (2010). First year students and the assessment of Information literacy at Barnard Lios. Retrieved fromhttp:/www.ala.org/mgrps/acrl/standard/informationliteracycompetence.cfm. Dadzie, P. S. (2005). Electronic resources: access and usage at Ashesi University College. Campus-Wide Information System, 22 (5), 290-297. Dickenson, D. (2006). How academic libraries help Faculty teach and students learn: The 2005 Colorado academic library impact study. Retrieved from http://www.LRS.org Edoka, B. E. (2000). Introduction to Library Science. Onitsha: Palma Publishing and Links Co. Ltd. Esse, U. C. (2014). Effects of library instruction on satisfaction with the use of library and its services: a study of undergraduate students in five universities in the southern part of Nigeria. European Scientific Journal Mayedition,10 (13),441-450.Retrieved from: http://eprints.covenantuniversity.edu.ng/7006/1/3368_9903_1_PB_Esse.pdf Ezemba, N. C. (2004). The essentials of library and information science. Ekwulobia: Theo Onwuka& Sons Publishers. pp. 71-104. Fagbola, B. O. (2015). Academic libraries and academic achievement of students in higher institutions. ASSEREN Journal of Educational Research and Development (AJERD), (1&2), 84-89. Federal Government of Nigeria (2013). National policy on education . Abuja: NERDC. Gakibayo, A., Ikoja-Odongo, J. R., Okello-Obura, C., &Gakibayo, (2013) "Electronic information resources utilization by students in Mbarara university library". Library Philosophy and Practice (e-journal). Paper 869.Retrieved From: http://digitalcommons.unl.edu/libphilprac/869 Ilo, M. &Idiegbeyan-ose B. (2011). Library user education programme for Covenant university freshmen: Impact, challenges and possible solutions. Samaru Journal of Information Studies, 11 (1 & 2.) Ilogho, J. E. Iroaganachi, M. (2012). Study skills and utilization of library resources by students of Gospel Faith Mission International Comprehensive High School, Ibadan Nigeria. Retrieved From: https. eprints.covenantuniversity.edu.ng/6519/ Kenya Projects Organization (2012). Sample Size Determination Using Krejcie and Morgan Table.Retrieved From: http://www.kenpro.org/sample-size-determination-using-krejcie-and-morgan-table/ Kumar, K. (2008). Library manual. New Delhi: Vikas Publishing House PVT Ltd. Mohammadi, M. Moghaddam, I. A. & Yeganeh, E. M. (2008). Students’ perception of the impact of user education on the use of reference resources: an Iranian experience. LibraryPhilosophy and Practice–ejournal.Retrieved from: http://www.webpages.uidaho.edu/ mbolin/mohammadi-moghaddam-yeganeh.htm Molstead Library (2014). Library services. Retrieved From: http://molstead.macminicolo.net/book/export/html/-117 Nagata, H., Toda, A. &Kytomaki, P. (2009).Students’ patterns of library use and their learning outcomes. Journal of the Japan Society of Library and Information Science, 53 (1) , 1-10. National Universities Commission (2018). List of approved Universities in Nigeria. NUC Bulletin Monday 5th March, 12 (4) 24-25. Nithyanandam, K., Kanniyappan, E., Dhankar, M. A. &Rajaseekar, V. (2006). User education programmes and academic libraries. Paper presented at the 4th International Convention CALIBER, Gulbarga between 2 nd to 4th February, INFUBENT Center, Ahmadabad Obidike, N. A. &Ekere, F. C. (2010). Ameliorating the constraints of information seeking in academic research: A study of social work lecturers and students at the University of Nigeria Nsukka. Unizik Journal of Research in LIS, 2 (1), 1-14 Obinyan, Martin Oziegbe&Udem, Obiora Kingsley, "NCE students’ perceptions on the use of library course as an aid to the use of library resources in South-West, Nigeria". Library Philosophy and Practice (e-journal).1877. Retrieved From: http://digitalcommons.unl.edu/libphilprac/1877 Obiozor, R., Ogbonna A. U. &Anyaegbu, M. (2007). Evaluating the use of university library resources by students and staff of Nnamdi Azikiwe University Awka. Unizik Journal of Research in LIS, 1 (1), 55-62. Ogbuiyi, S. U., Oriogu, C. D. &Ogbuiyi, D. C. (2013). Effects of information literacy skills and library user education on the use of information resources by undergraduate students of Babcock University, Nigeria. Nigerian Library and Information Science Review,22 (1&2), 56-65 Ogunmodede, T.A. &Emeahara, E.N. (2010). "The effect of library use education as a course on library patronage: A case study of LAUTECH library, Ogbomoso, Nigeria" Library Philosophy and Practice (e-journal). Paper 426. Retrieved From: http://digitalcommons.unl.edu/libphilprac/426 Ogunmodede, T. A., Adio, G. &Odunola, O. A. (2011). Library use education as a correlate of use of library resources in a Nigeria university. Retrieved From: http://unllib.unl.edu/LPP/ Onuoha, U. D.&Mosunmade, S. O. (2013). Undergraduates’ use of libraries in Federal Universities in South-West, Nigeria. IOSR Journal of Research &Method in Education (IOSR-JRME), 3 ( 5), 12-17. Retrieved From:www.iosrjournals.org Oyewusi, F. O. &Oyeboade, P. (2009). An empirical study of accessibility and use of library resources by undergraduates in a Nigerian State University of Technology. Library Philosophy and Practice (e-journal). Retrieved From: http:unlib.unl.edu/LPP/ Rasaki, O. E. (2008). A comparative study of credit earning information literacy skills courses of three African Universities. Library Philosophy and Practice Retrieved From: http://.www.webpages.vidaho.edu/rombolin/rasaki.htm Stone, G., Pattern, D. & Ramsden, B. (2011). Does library use affect student attainment? A preliminary report on the library impact data project. LIBER Quarterly. 21(1), 5–22. Retrieved From: http://doi.org/10.18352/lq.8005 Suleiman, S. A. (2012). User Education Programme in Academic Libraries: The Experience of the International Islamic University Malaysia Students. Library Philosophy and Practice. Retrieved from http://.unilib.unl.edu/Lpp/ Tella, A., Owolabi, K. A &Attama, R. O. (2009). Student use of the library: A case study of AkanuIbiam Federal Polytechnic Unwana, Nigeria.Chineese Librarianship: An International ElectronicJournal, 28. Retrieved From: http://www.icle.lis/clie:c/28TOA.pdf. Ukachi, B. N. (2013). Accessibility and students’ variables as correlates of the use of electronic information resources in university libraries in South-West, Nigeria. A thesis submitted to the Department of Library and Information Science, University of Nigeria, Nsukka, in fulfilment of the requirements for the award of the degree of Doctor of Philosophy (Ph.D) in library and information science Ukachi, B. N. (2011). Electronic information resources and undergraduate users’ patronage in University of Lagos Library: a Survey . Madonna Journal of Research in Library & Information Science,1 (2), .21-35. Unegbu, V. E. &Otuza, C. E. (2015). Use of library and information Resources: library use education.Retrieved From:SE%20OF%20LIBRARY%20AND%20INFORMATION%20RESOURCES%20(1pdf